Manajemen Praktik Kerja Lapangan SMK Muhammadiyah 2 Ponjong Bagi Keterserapan Lulusan Di Dunia Usaha dan Dunia Industri - Prihantini, Yeni; Purbonuswanto, Welius (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to: 1) know the planning of field work practices 2) organize field work practices 3) implement field work practices 4) evaluate field work practices at SMK Muhammadiyah 2 Ponjong. This research is a qualitative research. Data collection techniques include interviews, observation and documentation study. The data analysis technique used qualitative descriptive analysis including data collection, data reduction, data display and data verification. The results of this study: (1) planning of field work practices at SMK Muhammadiyah 2 Ponjong has been carried out well, such as in the activity planning stages, namely mapping KD taught in industry, mapping industry to determining industry, compiling field work practice programs, providing administration, conducting socialization and provision (2) organizing field work practices has been carried out well, namely the formation of field work practice working groups, the determination of supervisors, the placement of students in the industry. (3) the implementation has been carried out well including the stage of releasing students from field work practices, submitting students to field work practices, implementation, monitoring by the supervisor and submitting the results of activities 4) Evaluation has been carried out well including the stage of the student assessment process, analyzing student reports , and analysis of input from supervisors in the industry to determine student and industry satisfaction.